Tahfidz Al-Qur'an Learning System With Muqaththa'ah Method At Integrated Islamic SMP Ibnu Halim Medan - Fahmi Gunawan (Al-Ulum: Jurnal Pendidikan Islam, 2021)
This study aims to determine the Thafidz Al-Qur'an learning system with the Muqaththa'ah method at SMP Integrated Islamic Ibnu Halim Medan.This study used descriptive qualitative method. This thesis data collection technique uses the method of observation, interviews, and documentation. This research was discussed through a field study conducted at SMP Integrated Islamic Ibnu Halim Medan. The results of the research carried out concluded that the application of the Muqaththa'ah method in learning Tahfidz Al-Qur'an at SMP Integrated Islamic  Ibnu Halim Medan, for grade VIII SMP students were able to memorize the Al-Qur'an 1 juz, namely juz 30. The learning system used individually. in memorizing students' memorization in the period until the next class increase. And the implementation of learning is supported by 4 activities, namely opening prayer activities, core and closing activities, Tilawah and muraja'ah activities. There are 4 evaluations of learning, namely daily, weekly, midterm tests, and final semester tests. The evaluation is carried out by means of an oral test through rote memorization in this school which emphasizes the fluency of memorization and the law of tajwid as the main component in evaluating the quality of students' memorization of the Al-Qur'an and the Tahfidz Al-Quran learning program is also a requirement for student graduation. Keywords: Learning Tahfidz Al-Qur'an, Muqaththa’ah Method